2014
DOI: 10.1097/mao.0000000000000497
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Development of 2 Oral Languages by Child Cochlear Implant Recipients

Abstract: Despite the excellent hearing perception obtained with cochlear implants, the acquisition of a second language at home seems to slow down the development of the French mainstream language. Comparison of our results with those of previous studies indicates that bilingual children require intensive and correct input in both languages. Parents' involvement in rehabilitation efforts also appears as an important factor for successful oral language development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
0
20
1
Order By: Relevance
“…Studies of oral communication outcomes in children with bilingual language exposure who use CIs are limited, and there continues to be concern among families and professionals that exposure to two languages may have a negative impact on speech and language development in one or both of their languages (Deriaz, Pelizzone, & Pérez Fornos, 2014;Teschendorf, Janeschik, Bagus, Lang, & Arweiler-Harbeck, 2011). Existing studies involving bilingual CI users indicate that bilingual CI users are able to achieve bilingual oral proficiency (McConkey Robbins, Green, & Waltzman, 2004;Thomas, El-Kashlan, & Zwolan, 2008) and that they are able to match the language skills of their monolingual peers with CIs given that they receive support in their home language and the language of the majority (cf.…”
Section: Speech Production In Bilingual Children Who Use Cismentioning
confidence: 99%
“…Studies of oral communication outcomes in children with bilingual language exposure who use CIs are limited, and there continues to be concern among families and professionals that exposure to two languages may have a negative impact on speech and language development in one or both of their languages (Deriaz, Pelizzone, & Pérez Fornos, 2014;Teschendorf, Janeschik, Bagus, Lang, & Arweiler-Harbeck, 2011). Existing studies involving bilingual CI users indicate that bilingual CI users are able to achieve bilingual oral proficiency (McConkey Robbins, Green, & Waltzman, 2004;Thomas, El-Kashlan, & Zwolan, 2008) and that they are able to match the language skills of their monolingual peers with CIs given that they receive support in their home language and the language of the majority (cf.…”
Section: Speech Production In Bilingual Children Who Use Cismentioning
confidence: 99%
“…Prior to this study, some researchers found evidence for the benefits of supporting both spoken languages for bilingual children with HL (e.g., Bunta & Douglas, 2013; Guiberson, 2014), but other studies came to different conclusions in that focusing on the language of the majority and limiting home language input may be needed for children with HL exposed to two languages (e.g., Deriaz et al, 2014; Teschendorf et al, 2011). As Guiberson (2014) notes, when it comes to bilingual children with HL, it is not unusual to encounter “fear that bilingualism may splinter linguistic resources or result in linguistic confusion” (p. 87).…”
Section: Figurementioning
confidence: 93%
“…However, there is considerably less agreement both in the research literature and clinically regarding best practices when it comes to which spoken language to support in bilingual children with HL who use CIs and HAs (cf. Bunta & Douglas, 2013; Deriaz, Pelizzone, & Pérez Fornos, 2014; Guiberson, 2014; Rhoades & Chisolm, 2001; Teschendorf, Janeschik, Bagus, Lang, & Arweiler-Harbeck, 2011; Waltzman, McConkey Robbins, Green, & Cohen, 2003). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations